Tingkat Keterampilan Dasar Bermain Sepak Bola Peserta Didik Kelas VIII di SMP Negeri 2 Kupang Timur Tahun Ajaran 2022/2023 - Ermelinda Y.P. Larung; Damian Puling (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The purpose of the study was to determine the improvement of basic skills in the football game of students at SMP Negeri 2 East Kupang. This study is descriptive quantitative. With a population of 30 male students, SMP Negeri 2 Kupang Timur is a student. Research was conducted at the football field of Bouyant Bontessori Junior High School. The instrument used is a basic football skill test for 14-15 year olds from. The results of this study showed that the Basic Skill Level of Playing Football for Class VIII boys of SMP Negeri 2 East Kupang that the category was very high 6 participants by 30%; high category 5 students (25%) enough category 5 participants by 25%; low category 3 learners (15%) and very low category 1 learner (5%.).